Capability Development among the Ultra-poor in Bangladesh: A case study - Ahmed, Syed Masud (BMC, 2022)
This article was published in The Journal of Health, Population and Nutrition [©2009 © INTERNATIONAL CENTRE FOR DIARRHOEAL DISEASE RESEARCH, BANGLADESH] and the definite version is available at: https://doi.org/10.3329/jhpn.v27i4.3399 The Article's website is at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC2928093/